2012
DOI: 10.1515/mgmc-2012-0059
|View full text |Cite
|
Sign up to set email alerts
|

Complexes of germanium chlorides (RnGeCl4-n, n=0-3; R=Me, Ph) with redox active N-hetero­aromatic ligands: an electrochemical study

Abstract: Methyl and phenyl germanium chlorides (R n GeCl 4-n , n = 1, 2, 3), just like GeCl 4 , form complexes with electroactive bidentate (2,2 ′ -bipyridine) and monodentate (imidazole, pyrimidine and 2,6-dichloro-pyridine) ligands, R n GeCl 4-n ‧ L x (x = 1 or 2 for bi-and monodentate Ls, respectively), which were studied by cyclic voltammetry and electron paramagnetic resonance (EPR) spectroscopy supported by density functional theory (DFT) calculations. Dative interactions of lone pair of N of these heteroaromatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
(50 reference statements)
2
5
0
Order By: Relevance
“…For monochlorosilanes, this new system is assigned to (bipy·R 3 SiCl)/(bipy·R 3 SiCl) · couple. Similar anion radical complexes of 2,2'-bipy with poly-and monohalogermanes were recently reported [17].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For monochlorosilanes, this new system is assigned to (bipy·R 3 SiCl)/(bipy·R 3 SiCl) · couple. Similar anion radical complexes of 2,2'-bipy with poly-and monohalogermanes were recently reported [17].…”
Section: Resultssupporting
confidence: 85%
“…Thus, bipy-assisted silylation of carbon interfaces, free of inconvenience of pre-deposition of subnanolayers of transition metals, can be applied to a many commercially available mono-and poly-halo (Hal = Cl, Br, I) silanes. Similar anion radical complexes with 2,2'-bipy were recently reported for halogermanes [17]. Electrode passivation during their reduction, caused by the same phenomenon, means that germanium-tocarbon covalent grafting (via Ge-C bonds) can also be effected in the similar way.…”
Section: Resultssupporting
confidence: 73%
“…It is known that pyridine has extremely low electron affinity (−0.62 eV [24] ), which makes it difficult to reduce electrochemically (in particular, we found that it is irreversibly reduced at E p red =−2.990 V in acetonitrile). However, the withdrawing of electron density from it in donor‐acceptor bond allows us to expect that its reduction can be significantly facilitated (by analogy, for example, with derivatives of tetravalent germanium bonded to pyridine and its derivatives [25–27] ). Indeed, the CV curve of reduction of 2 shows a chemically irreversible peak at −2.256 V (Figure 2, Table 1), which is by 0.734 V (16.9 kcal mol −1 ) earlier than the reduction of pyridine.…”
Section: Resultsmentioning
confidence: 99%
“…As an example of a similar structural motif that reversibly attaches two electrons, we can mention the uorenone. 29 The results obtained can be compared with the electroreduction of chlorogermanes in the presence of 2,2 0 -bipyridine, 10 where the potential shi for various objects was also about 1 V. Comparable values of potential shis are observed in case of nicotinamide and isoniazid and their complexes with 3,5-di-tert-butyl germanium catecholate. 30 In case of nicotinic acid 30 and 3-and 4-cyanopyridines, the potential shi is 0.4-0.6 V. 31 At the same time, in all cases, complete chemical reversibility of electroreduction is not observed.…”
Section: Cyclic Voltammetrymentioning
confidence: 98%